Pendekatan Fenomenologi dalam Studi Islam - Sihabuddin Sihabuddin (Autentik : Jurnal Pengembangan Pendidikan Dasar, 2020)
Religion is the gift of God Almighty which is intended for humans (Muslims) as a guide to getsafety in the world and the hereafter, because in Islam there are rules that must be followed byindividuals and groups in order to distinguish between good (constructive-moralist) and which isbad (degradation-immoralis). Nevertheless, studying religion that collaborates science is notsomething that is prohibited. In fact, the correlation between religion and science is somethingthat is very likely to be carried by religious scholars, including in Islam. Understanding of theIslamic religion which has tended to be “theologically-normative” for decades has closed Islamicthinkers to study the phenomenon of Islam, such as understanding the practices of religiousteachings that tend to be ritualistic in each of the Muslims themselves. To understand it, aspecial method is needed called “phenomenology”, where this method describes the experienceof the religious practice of religious adherents consciously of the religious phenomena that arecarried out.